Development of NPP digital I&C system closed-loop online test system based on signal transmission array. (September 2018) - Yang, Minghan; Wang, Jianye; Chen, Shuai; Chen, Size; Zhang, Junjun
Abstract: With the development of process control technology, the digital Instrumentation and Control (I&C) system has been gradually adopted in the latest Nuclear Power Plants (NPPs). Accordingly, the digital I&C system test has become a key step during the NPP design phase. To effectively reflect the integrated performance, including the hardware, software, and interaction of the digital I&C system, it is necessary to adopt NPP operating data to drive the I&C system under test. NPP operating data can be obtained by a Full-Scope Simulator (FSS) merged into the test system. However, it is difficult to perform real-time conversion between the operating data in the memory of the FSS and the electrical signals in the I&C system. For this purpose, a closed-loop test system based on the Signal Transmission Array (STA)—a special signal generating and receiving device for communication between the FSS and I&C systems in real time—has been presented in this work. The initial development of this test system has been accomplished and is being used for China Lead-based Research Reactor (CLEAR-I) digital I&C system. The results show that the test system based on the STA can trace variations of the operation data of the NPP and electrical signals of the digital I&C system and is able to reveal the control performance and failure characteristics.